Association between family history, mutation locations, and prevalence of BRCA1 or 2 mutations in ovarian cancer patients. (1st March 2019) - Singer, Christian F.; Tan, Yen Y.; Muhr, Daniela; Rappaport, Christine; Gschwantler‐Kaulich, Daphne; Grimm, Christoph; Polterauer, Stephan; Pfeiler, Georg; Berger, Andreas; Tea, Muy‐Kheng M.
Abstract: We investigated the prevalence of germline BRCA mutations in a population‐based cohort of Austrian women diagnosed with ovarian cancer and its association with family history of cancer. We prospectively collected family pedigrees of 443 Austrian ovarian cancer patients who had been tested for the presence of a germline BRCA or 2 mutations and correlated the familial breast and ovarian cancer burden with the prevalence of BRCA mutations and disease onset. The probability of carrying a g BRCA mutation in patients without family history of cancer is 14% (95% CI 9%‐22%), as opposed to 45% (95% CI 31%‐59%) of patients with at least one family member with ovarian cancer, and 47% (95% CI 40%‐54%) if other relatives have developed breast cancer. If both breast and ovarian cancer are diagnosed in the family, the probability of carrying a germline BRCA1 or 2 mutations is 60% (95% CI 50%‐68%). germline BRCA1 or mutations in families with ovarian cancer only are commonly located in the Ovarian Cancer Cluster Regions when compared to families with both breast and ovarian cancer ( P  = 0.001, and P  = 0.020, respectively). While g BRCA mutation carriers with ovarian cancer do not have a significantly different age at onset than patients with a family history of cancer, g BRCA1 carriers in general have an earlier onset than g BRCA2 carriers ( P  = 0.002) and patients without a mutation ( P  = 0.006). The rate of germline BRCA1 or 2 mutations in ovarian cancer patients without a family history or breast or ovarian cancer is low. However, in women with additional family members affected, the prevalence is considerably higher than previously reported. Abstract : Our study assessed BRCA1 or 2 mutations in ovarian cancer patients and its association with family history of cancer and mutation locations. Our findings may direct genetic counseling and/or testing for family members of ovarian cancer patients whose BRCA1 or 2 testing results are not available.